Particle Swarm Optimization in Health Care Domain - Chauhan, M S (Annals of the Romanian society for cell biology, 2021)
Document by Subject Area:There are a lot of publications in different fields of engineering, computer & materials sciences, mathematics, physics, chemistry, agricultural and biological sciences, chemical engineering, environmental science etc. From the above table, it is clear that there are 88 number of publications in Engineering, 68 in Computer Science, 42 in Mathematics, 12 in Energy, 11 in Materials Science and Physics and Astronomy, 7 in Chemistry, 6 in Chemical Engineering, Environmental Science, Agricultural and Biological Sciences respectively. [...]engineering has maximum number of publications as compared with all. An optimal scheduling of patients that minimizes patient stay in the hospital enhances patient care, resource utilization and hence reduces anxiety conflicts between employers and family members. [4] U. Singh, R. Salgotra, and M. Rattan, "A Novel Binary Spider Monkey Optimization Algorithm for Thinning of Concentric Circular Antenna Arrays," IETE J. Res., vol. 62, no. 6, pp. 736-744, 2016.